2020
DOI: 10.1088/1681-7575/ab8829
|View full text |Cite
|
Sign up to set email alerts
|

Correction factors for two new reference beta radiation fields

Abstract: Several correction factors for two new reference beta-particle radiation fields complementing ISO 6980 have been measured and calculated for both primary beta dosimetry and the operational quantities in radiation protection. The following correction factors for primary beta dosimetry for the determination of the absorbed dose to tissue, D t, have been determined by calculations: k ba for backscatter from the collecting electrode, k pe for perturbation by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…A similar comparison for 4 mmthick PMMA flattening filter shows deviations increase to about 0.6-0.7%. However, the values published by Behrens [42], show good agreement (within 0.1%) with the Monte Carlo-calculated values for both the PMMA flattening filters. PET Filter [33].…”
Section: Jinst 16 P03006supporting
confidence: 71%
See 3 more Smart Citations
“…A similar comparison for 4 mmthick PMMA flattening filter shows deviations increase to about 0.6-0.7%. However, the values published by Behrens [42], show good agreement (within 0.1%) with the Monte Carlo-calculated values for both the PMMA flattening filters. PET Filter [33].…”
Section: Jinst 16 P03006supporting
confidence: 71%
“…Note that it has been previously demonstrated that Bragg-Gray values are independent of 𝑙 [31,32]. Also presented in tables 8 and 9 are published values reported in literature [6,31,42]. The Monte Carlo-calculated Bragg-Gray values at 70 μm depth with PET flattening filter and without filter compare well with the ISO-mentioned values for all the sources (within 0.2% for 90 Sr/ 90 Y source at 50 cm with PET and 147 Pm source at 20 cm with PET).…”
Section: Bragg-gray Stopping-power Ratio Of Tissue-to-airmentioning
confidence: 82%
See 2 more Smart Citations
“…Several computational MC codes are widely well known and used for radiation dosimetry such as, PENELOPE, GEANT4, FLUKA, EGSnrc, MCNP and others [8][9][10][11][12]. It is possible to find in literature publications reporting results on MC modelling and simulations using the varies MC codes available, of beta dosimetry systems with different types of extrapolation chambers [13][14][15][16][17][18][19][20][21][22]. However, there is no publication,…”
Section: Introductionmentioning
confidence: 99%